A general algorithm for multiple-sets split feasibility problem involving resolvents and Bregman mappings. (1st February 2018) - Raeisi, M.; Zamani Eskandani, G.; Eslamian, M.
Abstract : In this paper, by using Bregman distance, we introduce a new iterative process involving products of resolvents of maximal monotone operators for approximating a common element of the set of common fixed points of a finite family of multi-valued Bregman relatively nonexpansive mappings and the solution set of the multiple-sets split feasibility problem and common zeros of maximal monotone operators. We derive a strong convergence theorem of the proposed iterative algorithm under appropriate situations. Finally, we mention several corollaries and two applications of our algorithm.